Flanagan's version: A spectator's guide to science on the eve of the 21st century - Flanagan, Dennis (New Delhi Affiliated East-West Press, 1988)
Individual chapters review recent progress in physics, astronomy, geology, biology, technology, and pseudoscience.
Keywords: Modern science; philosophy of science; Science history